Assessment of Drought Hazard: A Case Study in Sampean Baru Watershed, Bondowoso Regency - Putra, Victorius Setiaji; Halik, Gusfan; Agung Wiyono, Retno Utami (Universitas Negeri Semarang, 2021)
Abstract. The Sampean Baru watershed is categorized as an area with a very high level of vulnerability to drought. The purpose of this study was to assess the hydrological drought in the Sampean Baru watershed. NCEP / NCAR Reanalysis climate change data is used to obtain synthetic rainfall models of the past. This climate change data has crude resolution and is global in scale. The NCEP / NCAR Reanalysis data was processed through a downscaling process to obtain local scale climate data in the form of past synthetic rains. Artificial Neural Network (ANN) is one of the downscaling models used in this study. The ANN downscaling output was processed through discharge modeling using SWAT. Hydrological drought assessment used the Standardized Precipitation Index (SRI) method. The SRI calculation was based on the accumulated discharge over a period of time. The results indicated that the ANN downscaling process can bridge global scale climate data to local scale climate data. SWAT modeling gave excellent results. SRI-6 can describe past droughts. It can be seen from the compatibility between the results of the drought assessment and the drought data belonging to the relevant authorities.